Thinking the unthinkable : the modernization and reform of Islamic higher education in Indonesia - Farish A. Noor (2009)
The reform and modernization of Higher Islamic Education has been an ongoing concern for many a Muslim-majority state since the advent of modern Islamic studies in the postcolonial era.